Counter Mode Development for Block Cipher Operations - Ali Sagheer (Al-Rafidain Journal of Computer Sciences and Mathematics)
There are two basic types of symmetric algorithms: block ciphers and stream ciphers. Block ciphers operate on blocks of plaintext and ciphertext—usually of 64 bits but sometimes longer. Stream ciphers operate on streams of plaintext and ciphertext one bit or byte (sometimes even one 32-bit word) at a time. With a block cipher, the same plaintext block will always encrypt to the same ciphertext block, using the same key. With a stream cipher, the same plaintext bit or byte will encrypt to a different bit or byte every time it is encrypted. In this paper we introduce three developments of Counter Mode of Operation of Block cipher. These developments merge between advantages of Counter Mode with other Modes. This gives a good secure Modes for General purpose block-oriented transmission Authentication, Random access, Stream-oriented transmission over noisy channel.